Pain symptoms in depressed outpatients - Ahmad Qabil, Khalib (2009)
Major depressive disorder is an important health problem and a major cause of disability worldwide. There is a strong association between depression and pain, which is influenced by various biological and psychosocial mechanisms. The combination of chronic pain and depression is associated with high rates of disability, socioeconomic disadvantage, greater utilization of health care resources, as well as a considerable mortality rate. (a) To determine the proportion of adult depressed patients attending the psychiatric clinic who have pain symptoms, (b) to assess the characteristic of personality traits in the respondents, (c) to determine the association between specific personality traits and pain symptoms in the respondents, and (d) to determine the association between depression and pain symptoms in the respondents.A survey was carried out on patients aged 18 years and above with a diagnosis of major depressive disorder according to Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), who attended the psychiatric clinic in Hospital Universiti Sains Malaysia. Convenience sampling was carried out during the study period between February 2008 and June 2009. The questionnaires utilized were the sociodemographic data form, Hamilton Rating Scale for Depression (HAM-D), Brief Pain Inventory (BPI) - Malay version, and Crown-Crisp Experiential Index (CCEI) - Malay version, which were filled after obtaining written informed consent. Patients who refused to give consent, those with co-morbid psychiatric diagnosis and those with medical or surgical conditions associated with pain symptoms were excluded from the study. 51 respondents were included in this study. Overall, the respondents in this study had mild levels of depression, and about half had neurotic traits. 80.4% of respondents experienced pain, but overall the severity of pain in the group was mild. When compared by the presence of pain, there was no difference in the sociodemographic characteristic. However, Fisher's chi-square test revealed statistically significant difference in the status of depression (depressed versus remitted) and "anxious depression" characteristic, whereby those who were still depressed (p < 0.05) and those with "anxious depression" (p < 0.05) were more likely to experience pain. Logistic regression analysis of sociodemographic and clinical variables did not show any statistically significant finding with regard to their status of pain presence or absence. There was positive correlation between the Free floating anxiety (FF A) (r = 0.363, p = 0.009), Somatic concomitants of anxiety (SOM) (r = 0.394, p = 0.004), and Depression (DEP) (r = 0.478, p < 0.001) sub-scales ofCCEI as well as CCEI total score (r = 0.41 5, p = 0.002) with the severity of pain. The CCEI total score accounts for 17.2% of the variance of BPI total score. Twelve items from the HAM-D pertaining to depressed mood and various types of anxiety (including "depressed mood", "work & interests", "psychic anxiety", "somatic anxiety", "general somatic" and "genital symptoms"), as well as HAM-D total score (r = 0.608, p < 0.001) were positively correlated with severity of pain. The HAM-D total score accounts for 33.2% of the variance of BPI total score. The proportion of adults with major depressive disorder having pain is 80.4 per cent. This study shows there is association between anxiety, personality traits and severity of depression with the severity of pain experienced by depressed patients.